Revisiting Islamic Legal Politics under the New Order: Insights from Islamic Civilizational Thought - Zulkifli Nas; Heri Firmansyah (TSAQAFAH, 2025)
The New Order era marked a new chapter in Indonesian politics. During this period, the relationship between Islam and the state experienced a dynamic of ebb and flow. This study aims to identify and analyze the political influences on the legislation of Islamic law, and to explain why the New Order, which was initially hostile to political Islam, ultimately accommodated Muslim aspirations. This research employs a library-based study approach, tracing and analyzing data from books, journals, and secondary sources related to the politics of Islamic law during the New Order. A historical-analytical approach is used to examine the chronology of relevant events and political dynamics. The study finds that the legislation of Islamic law during the New Order was shaped by three key factors: first, a renewal in Islamic political thought from a confrontational, formalistic approach to a substantive, accommodative one; second, the strengthening political role of the Muslim community within the state's power structure; and third, a change in the New Order's internal political configuration, specifically the weakening of President Soeharto's control over the military, which prompted him to seek a new political alliance with the Muslim community as a base of support. The result of this interaction was the legislation of four legal products that aligned with the interests of the Muslim community: the National Education System Law, the Religious Courts Law, the Compilation of Islamic Law, and the establishment of Bank Muamalat Indonesia.